DESIGNING AND APPLICATION OF RESTRAINING GADGETS – INNOVATIVE TOOLS TO HANDLE POISONOUS SNAKES - N.V. Rajesh; M.G. Jayathangaraj; M. Raman; R. Sridhar (Indian Journal of Veterinary and Animal Sciences Research, 2024)
Restraining gadget for Indian poisonous snakes like Indian cobra and Russell’s Viper were designed, using available infrastructures. Tongs, collapsible tubes and bags were designed and applied in the poisonous snakes in order to have better restraining activities. These snakes reared at Guindy Snake Park Trust were successfully restrained, using the gadgets developed. However these gadgets were found not suitable for restraining procedure associated with Saw scaled viper and Common krait. The gadgets developed were useful for zoo veterinarians for control of these serpentines.